The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/aac.03135-14
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Nucleic Acid-Based Reporter System To Detect Mycobacterium tuberculosis Antibiotic Sensitivity

Abstract: bWe previously reported the development of a prototype antibiotic sensitivity assay to detect drug-resistant Mycobacterium tuberculosis using infection by mycobacteriophage to create a novel nucleic acid transcript, a surrogate marker of mycobacterial viability, detected by reverse transcriptase PCR (M. C. Mulvey et al., mBio 3:e00312-11, 2012). This assay detects antibiotic resistance to all drugs, even drugs for which the resistance mechanism is unknown or complex: it is a phenotypic readout using nucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Therefore, upon infection, relatively long incubation times are need it. This was cleverly resolved by Mulvey and collaborators by focusing on the detection of RNA molecules synthetized by a highly-transcribed phage-borne artificial cassette instead of detecting phage DNA [10,16]. Due to the fact that the number of phage RNA molecules produced per infected cell generally far exceeds the number of new phage DNA genomes, we explored the possibility of developing phage RNA detection as a reliable and rapid diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, upon infection, relatively long incubation times are need it. This was cleverly resolved by Mulvey and collaborators by focusing on the detection of RNA molecules synthetized by a highly-transcribed phage-borne artificial cassette instead of detecting phage DNA [10,16]. Due to the fact that the number of phage RNA molecules produced per infected cell generally far exceeds the number of new phage DNA genomes, we explored the possibility of developing phage RNA detection as a reliable and rapid diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, detection methods based on the reverse transcription of highly abundant RNAs show better LOD and are less prone to false positives than DNA detection assays [15]. Interestingly, Mulvey et al [10,16] reported the use of TM4 genetically engineered phages for the detection and antibiotic susceptibility determination of Mycobacterium tuberculosis. In this assay, the phage delivers heterologous cassette(s), "surrogate marker loci" (SML), designed to produce high RNA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Various alternative AST methods have been described in recent years, including nucleic acid-based ASTs. These nucleic acid-based ASTs are performed by determining either the bacterial chromosomal DNA copy number using qPCR or phage-specific mRNA transcript copy number using qRT-PCR (Waldeisen et al, 2011 ; Mulvey et al, 2015 ). However, these assays are still growth dependent and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Several assays used enzymes to catalyze the generation of their respective biomarkers. Using this method, two endpoints have been explored: the detection of changes in electric current [28,29] and the detection of unique nucleic acid sequences [30,31]. One approach used reporter phages to introduce the enzyme [31], whereas another used an enzyme already present in mycobacteria [30].…”
Section: Mycobacteriophages As Diagnosticsmentioning
confidence: 99%